A macroprolactinoma becoming resistant to cabergoline and developing atypical pathology. (18th October 2016) - Sbardella, Emilia; Farah, George; Fathelrahman, Ahmed; Cudlip, Simon; Ansorge, Olaf; Karavitaki, Niki; Grossman, Ashley B
Summary: Pituitary adenomas are a common intracranial neoplasm, usually demonstrating a benign phenotype. They can be classified according to pathological, radiological or clinical behaviour as typical, atypical or carcinomas, invasive or noninvasive, and aggressive or nonaggressive. Prolactinomas account for 40–60% of all pituitary adenomas, with dopamine agonists representing the first-line treatment and surgery/radiotherapy reserved for drug intolerance/resistance or in neuro-ophthalmological emergencies. We present the case of a 62-year-old man with an apparently indolent prolactin-secreting macroadenoma managed with partial resection and initially showing a biochemical response to cabergoline. Five years later, the tumour became resistant to cabergoline, despite a substantial increase in dosage, showing rapid growth and causing worsening of vision. The patient then underwent two further transsphenoidal operations and continued on high-dose cabergoline; despite these interventions, the tumour continued enlarging and prolactin increased to 107 269 U/L. Histology of the third surgical specimen demonstrated features of aggressive behaviour (atypical adenoma with a high cell proliferation index) not present in the tumour removed at the first operation. Subsequently, he was referred for radiotherapy aiming to control tumour growth. Learning points: The development of secondary resistance to dopamine agonists (DAs) is a serious sign as it may be associated with de-differentiation of the prolactinoma and thus of aggressive or malignant transformation. Significant de-differentiation of the adenoma documented on consecutive histologies suggests a possible transition to malignancy. A combination of histological 'alarm' features associated with persistent growth and escape from DAs treatment in recurrent adenomas should alert clinicians and demands close follow-up. A multidisciplinary approach by pathologists, endocrinologists and neurosurgeons is essential.